Rotation capacity of bolted flush end-plate stiffened beam-to-column connection = Zdolność do obrotu użebrowanego połączenia z blachą wpuszczoną belki ze słupem - Ostrowski, Krzysztof; Kozłowski, Aleksander (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the flexibility parameters of semi-rigid joints is rotation capacity. Plastic rotation capacity is especially important in plastic design of framed structures. Current design codes, including Eurocode 3, do not posses procedures enabling designers to obtain value of rotation capacity.
Keywords: rotation capacity; FEM analysis; hierarchical validation; numerical experiment; zdolność do obrotu; analiza MES; walidacja hierarchiczna; eksperyment numeryczny